Electromagnetic shielding properties of polymer blended with graphene sheets and iron oxide particles - Mourad Makhlouf; Sabrina Bouriche; Zoubir Benmaamar; Didier Villemin (Revue des Énergies Renouvelables)
This work introduces an innovative polymer composite for electromagnetic interference (EMI) shielding, combining recycled graphene sheets and iron oxide (Fe2O3) particles within a PVC matrix. The goal was to develop a lightweight and effective material to attenuate electromagnetic disturbances, particularly in the band frequency range (10-15 GHz). An ultra-thin (2 mm) composite containing only 10% recycled graphene, obtained from spent batteries, achieved electromagnetic shielding effectiveness (SE) of 38.5 dB in this frequency band. This result demonstrates a significant synergy between graphene and Fe2O3, where the addition of Fe2O3 enhanced graphene dispersion via ligand exchange, thereby lowering the percolation threshold and increasing wave absorption. These key findings highlight the potential of this composite for EMI shielding applications in high-stress environments. Future research perspectives include optimizing the graphene/Fe2O3 composition to further enhance shielding effectiveness, exploring the impact of different Fe2O3 morphologies, and evaluating the environmental stability and durability of the composite under various operational conditions. Furthermore, investigating the integration of this composite into specific electronic devices, such as 5G communication systems and wearable devices, will validate its practical application and commercial potential.